Treatment of Capitellum and Trochlear Fracture using Headless Screw with Concomitant Olecranon Fracture Through Posterior Approach: A Case Report - Aishah NZA; Noor HA (Malaysian Orthopaedic Journal)
Articular fracture of distal humerus account for 2% of all adult elbow fracture. The coronal shear fracture combined with olecranon fracture require stable anatomical reduction and stabilisation for early rehabilitation and mobility. Numerous reports have described various approaches in tackling this type of fracture and method of fracture fixation. Here, we shared a case of a lady with traumatic coronal shear capitulum and trochlear comminuted fracture fixed using posterior elbow approach with fracture site open window technique in managing distal humerus articular fracture with ipsilateral olecranon fracture using headless screw and tension band wire. During last follow-up, fracture was united radiographically with congruent articular joint, patient able to return to her original function without limitation and no indications of avascular necrosis.